1987
DOI: 10.1152/ajprenal.1987.253.3.f394
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypercapnia enhances Vmax of Na-H antiporter of renal brush-border membranes

Abstract: Chronic hypercapnia is associated with increased proximal HCO3 reabsorption that is thought to be mediated by a Na-H antiporter. We hypothesized that chronic hypercapnia would be associated either with increased Vmax or with decreased Km of the Na-H antiporter. To test this hypothesis we made rabbits hypercapnic for 48 h by exposure to 10% CO2. In both control and hypercapnic animals, cortical luminal membranes were enriched over the homogenate 16-fold in alkaline phosphatase and 10-fold in maltase activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…The present studies establish the cellular mechanism of the increased bicarbonate reabsorption in the proximal tubule in response to chronic respiratory acidosis: adaptation to chronic respiratory acidosis involves stimulation of the luminal Na/H antiporter and the basolateral Na/(HCO3)3 cotransporter. They agree with studies using brush border membrane vesicles from rabbit renal cortex which have found an increase in Na/H antiporter activity induced by chronic respiratory acidosis (9,32).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present studies establish the cellular mechanism of the increased bicarbonate reabsorption in the proximal tubule in response to chronic respiratory acidosis: adaptation to chronic respiratory acidosis involves stimulation of the luminal Na/H antiporter and the basolateral Na/(HCO3)3 cotransporter. They agree with studies using brush border membrane vesicles from rabbit renal cortex which have found an increase in Na/H antiporter activity induced by chronic respiratory acidosis (9,32).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the present studies were designed to examine whether chronic respiratory acidosis affects the rates of the luminal Na/H antiporter and the basolateral Na/(HCO3)3 cotransporter. In vesicle studies, increased Na/H antiporter activity has been reported by one group (9), but not confirmed by others (10,11). Animals in which chronic respiratory acidosis was induced were compared to controls.…”
Section: Introductionmentioning
confidence: 77%
“…These Na+ concentrations greatly exceed the Na+/H' antiport Km for Na+ (I 51 mM) (52); thus it is extremely unlikely that the measured increase in Na + / H + antiport activity using these experimental conditions represents anything other than an increase in the V. of the antiporter. Concordant with this conclusion, in almost all instances, sustained increases in Na+/H+ antiport activity in response to a variety ofbiological stimuli have been associated with an increase in antiporter Vm., which in some instances has been associated with increased synthesis of transporters (55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Sci. USA 87 (1990) also been found by some investigators to cause an increase in Na/H antiporter activity (15)(16)(17). In the next series of studies, we performed experiments similar to those described above, with the exception that acid medium was identical to control medium, and acid cells were placed in a 10% C02/ 90% air incubator while control cells were placed in a 5% C02/95% air incubator.…”
mentioning
confidence: 87%